Imaginative Moods Aesthetics, Religion, Philosophy - Jorgensen, Dorthe (Book collections on Project MUSE., 2021)
Following modern and postmodern philosophys critique of metaphysics, experiences of transcendence are often considered aesthetic rather than metaphysical. However, aesthetics is mostly identified with the study of art, and aesthetic phenomena are considered particularly sensuous. This book criticizes such an approach to aesthetics, which has led many philosophers and theologians to neglect or reject aesthetics as a philosophical or theological discipline. It demonstrates how contemporary philosophy and theology may benefit from studying the mind-opening and world-transformative nature of our experiences of transcendence. In addition, it presents the significance of such experiences for the understanding of, for example, art, faith, prayer, presence, beauty, sensitivity, imagination, receptivity, and divinity. Imaginative Moods: Aesthetics, Religion, Philosophy is related to the simultaneously published monograph Poetic Inclinations: Ethics, History, Philosophy . Together they constitute a comprehensive presentation in English of the author s philosophy of experience, which includes new ways of conceiving of and applying aesthetics, hermeneutics, and phenomenology, and of integrating these disciplines, as well as theology.